감염병의 범세계적 유행에 대한 교양 생물학 교수-학습 모듈 제안 - 조은희(Cho, Eun Hee) (교양교육연구, 2020)
이 연구에서는 ‘과학적 소양의 함양’이라는 교양 과학 교육의 목표를 구체화한 다음 이를 최대한반영하여 바이러스성 감염병의 범세계적 유행을 이해하고 합리적인 대처 방안을 모색하는 다학제적교수-학습 모듈을 제안한다. 수업을 통해서 학생들은 우리 사회가 전염병의 대유행에 대처하면서 의사결정을 내릴 때, 어떤 종류의 과학지식이 어떻게 활용되는지, 그리고 과학 연구를 통해 알게 된 사실들이우리의 일상과 제도를 어떻게 바꾸고 있는지 살펴볼 수 있을 것이다. 이 수업에서 담당 교수는 코로나바이러스감염증-19의 유행이 어디에서 비롯되었고, 어떻게 진행되고 있으며, 앞으로 어떻게 대처해야 할지에대해 조망하고, 관련 정보가 산출된 과정과 신뢰할 만한 자료의 목록을 제시하는 안내자의 역할을한다. 수업에서 학생들은 스스로 탐구 질문을 설정하고 이에 대한 답을 찾아가며 새로운 지식을 익히고해결 방안을 모색한다. 이 과정을 통해 문제를 해결하는 과정에는 다양한 분야의 협력이 필수적임을체감하고, 과학 활동이 이루지는 과정과 성과의 의미를 이해하는 동시에, 자료의 신뢰성을 평가하여믿을만한 자료를 찾아 비판적으로 읽는 훈련이 가능하다. 마무리 단계에서는 코로나바이러스에 대한취약계층에 해당하는 부모나 조부모의 궁금증을 풀어주는 과제를 통해 자신이 학습한 내용을 주변과공유하고 소통하는 기회를 갖는다. 이 모듈은 교양 생물학 또는 교양 과학 교과에서 5주 정도의 기간에적용하기에 적합한 구성이며, 수업의 성격이나 학생들의 관심 영역에 따라 다양한 방식으로 변형하여활용할 수 있다. 본 연구의 제안이 학생들의 과학적 소양 함양을 목표로 하는 교양 교과목을 설계하고운영하는데 도움이 되기를 기대한다. This study proposes a teaching and learning module on the pandemic diseases within the undergraduate general biology curriculum. The study specifies that the goals of the class are to promote scientific literacy, and devises contents and methods that could achieve those goals. Students will become aware of the kind of scientific knowledge used to cope with the COVID-19 as well as to learn how the facts garnered from scientific research change our daily lives and society at large. In class the lecturer gives a brief overview on where the COVID-19 originated from, how it is progressing, and how it can be dealt with in the future. He or she should also provide a list of reliable sources of relevant information pertaining to this virus and its spreading patterns. By encouraging students to ask their own questions, they can gain new knowledge and find reasonable solutions to current issues. Through this process, students will be able to appreciate the importance of multidisciplinary cooperation in various fields, understand the process of science, and become better equipped with the ability to search for reliable information. In the final stage, students are asked to interview their family members about the COVID-19 as an opportunity to communicate and share their knowledge with their parents and grandparents, all of whom are more vulnerable to the virus. This module is designed as a 5-week program suitable for general biology courses, and can be modified to suit the nature and the goals of various other classes. The module can contribute to cultivating science literacy in general biology courses by guiding the design and operation of those courses. KCI Citation Count: 1